PEMBINAAN SADAR WISATA DAN GROOMING UNTUK ANGGOTA POKDARWIS DI PULAU NGENANG - Dewi Aurora Mikasari; Rezki Alhamdi; Syafruddin Rais; Erni Karlina (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
Ngenang Island, Nongsa District, Batam City is a tourist destination that has a variety of natural wealth that has not been visited by enough domestic or foreign tourists. Awareness of tourism from the community and the readiness of the community in one of its supporting elements, namely human resources, especially in terms of grooming, is expected to be one of the auxiliary values in increasing the flow of tourists, especially on Ngenang Island. Referring to the above, it is felt that it is necessary to develop tourism awareness and grooming for members of POKDARWIS Ngenang Island. It is necessary to conduct a SWOT analysis (Strength, Weakness, Opportunity and Threat) so that POKDARWIS and other tourism drivers on Ngenang Island get a deeper analysis of what are the potentials and opportunities that can be achieved in the future in order to increase their tourism potential. From the mapping and initial hearings carried out before the activity and during the activity, the material was focused on public awareness of tourism and the importance of grooming elements, especially on the frontline / frontliner of Ngenang Island tourism